Penguatan Karakter Siswa Melalui Strategi Pencegahan Perilaku Menyimpang di Sekolah Menengah Kejuruan Negeri 2 Gorontalo Utara - Ariyanto Nggilu; Abd Firman Bunta; Nurul Mawahda (Civic Education Law and Humaniora : Jurnal Pengabdian Masyarakat Terintegrasi, 2025)
Deviant behavior among vocational school students presents a challenge that hinders the implementation of education and character building, necessitating systematic and sustainable prevention strategies. This community service activity was conducted at SMK Negeri 2 North Gorontalo with the aim of increasing students' understanding of the impacts of deviant behavior and strengthening the school's capacity to promote a culture of discipline and positive character. The method used was community education through outreach, mentoring, and involvement of school stakeholders. The activity stages included preparation, coordination, implementation, and preparation of a post-activity report. The results showed that this program not only increased students' knowledge about the dangers of behavior such as smoking, bullying, and truancy, but also strengthened the commitment of teachers as key actors in character education. Ongoing mentoring is planned to ensure that changes in student attitudes are stable and measurable. This activity recommends integrating character education into the curriculum, increasing teacher capacity, regular monitoring, and collaboration between schools and parents as long-term preventive strategies.